Využití projektové metody ve výuce kulturních studií - Roebuck, Olga; Černá, Monika (Univerzita Pardubice, 1998)
This short article describes a new and unique way of raising inter-cultural awreness. The described Cultural studies programme was designed at the Institute of languages and humanities of the University of Pardubice several years ago and has been successfully continuing till today. The article contains a thourough description of the course and a discussion of its pros and cons. The research examining the effectiveness of the course (being carried out at the moment) is also mentioned.
Keywords: výuka; projektová metoda; kulturní studia; reálie